Diferença entre as espécies de Timbó (Derris Spp., Fabaceae) de diferentes regiões da Amazônia no controle da Musca domestica L. - Costa, José Paulo Chaves da; Belo, Muracy [UNESP] (Instituto Nacional de Pesquisas da Amazônia, 1999)
The roots' powder of timbo species collected in different regions of Amazonia that were tested in larvae groupings, didn't produce differential significative effects in two strains of Musca domestica. The two species with the greater number of plants used in the trial were Derris urucu and Derris nicou; the individuals from the species came from regions considered as "forestal refugies" during the Amazonian pleistocene. Among each species the plants varied since that inefficient to control, until plants lethals to the fies. This differential capacity for larvae control among plants of the same species, originated from different regions, suggests that both species had their populations isolated, during the quaternary epoch. In regions or "forestal refugies", where both species were represented, D. urucu was superior to D. nicou in the capacity to control larvae. While among plants from F region (Peruvian-East refuge) of the State of Acre, the two species had convergence in the values of damage to larvae groupings. Among the another species, Derris sp. (yellow timbo or watermelon timbo) didn't show differences in larvae control between samples from the two regions; while the species that was introduced in the Amazonia Denis elleptica showed damage in the larvae groupings similar to the most effective plants of D. nicou and D. urucu.

O pó das raízes das espécies de timbó coletadas em diferentes regiões da Amazônia, testado em agrupamentos de larvas, não produziu efeito diferencial significativo entre duas linhagens de Musca domestica. As duas espécies com maior número de plantas empregadas foram Derris nicou e Denis urucu; seus representantes são provenientes de regiões que foram consideradas como refúgios florestais, durante o plcistoceno na Amazônia. Dentro de cada espécie, as plantas variaram, desde aquelas ineficientes, até as que foram altamente letais no controle das moscas. Esta capacidade diferencial no controle das larvas entre plantas da mesma espécie, originadas de regiões diferentes, sugere que ambas as espécies devem ter apresentado isolamento de suas populações, durante esta época do quaternário. Nas regiões ou refúgios florestais, onde essas espécies estiveram representadas, D. urucu foi superior a D. nicou na capacidade de controlar as larvas. Enquanto, entre as plantas da região F (refúgio do Leste-peruano), do Estado do Acre, as duas espécies apresentaram convergência de valores, dos danos produzidos nos agrupamentos de larvas. Entre as outras espécies, Derris sp. (timbó amarelo ou melancia) não apresentou entre as amostras provenientes de duas regiões, diferenças nos efeitos às larvas; enquanto, a espécie introduzida na Amazônia, Derris elliptica, mostrou danos nos agrupamentos de larvas, semelhantes a algumas das melhores plantas de D. nicou e D. urucu.
Differences among Timbo (Derris spp. Fabaceae) species from different Amazonian regions in the control of Musca domestical L.
Keywords: Amazonia; Control; Florestal refugies; Musca domestica; Timbo; Amazônia; Controle; Musca domestica; Refúgios Florestais; Timbó